Sleep quality, mental health, and cognitive function among older adults in Chinese communities: a cross-sectional study - Fu, Wangsheng; Li, Wei (Frontiers in Public Health, 2025)
BackgroundAdequate and good sleep is essential for improving mental health and cognitive function in older adults. However, there is a lack of research on the relationship between sleep and psychiatric symptoms and cognitive function in the Chinese older adult population.MethodsA total of 621 community older adults aged 60 and older were included in the current study. The Pittsburgh Sleep Quality Index (PSQI), Geriatric Depression Scale (GDS), Self-rating anxiety scale (SAS), and Montreal Cognitive Assessment Scale (MoCA) were administered to all the participants. Based on PSQI, the research subjects were divided into the good sleep quality group and the bad sleep quality group. Moreover, 48 healthy individuals without mild cognitive impairment and dementia also accepted brain MR imaging.ResultsThe prevalence of poor sleep was 49.9%, and age, physical exercise, traumatic brain injury as well as family history of sleep disorders were associated with poor sleep (p < 0.05). Poor sleepers demonstrated higher prevalence of anxiety and depressive symptoms than good sleeper (p < 0.05). In a subgroup analysis of magnetic resonance, individuals with poor sleep quality had higher left and right transverse temporal cortex thickness and higher scores on the GDS and SAS scales. The results of linear regression analysis showed that the total score of SAS was correlated with the thickness of the left transverse temporal gyrus (T = 2.115, p = 0.042).ConclusionAbout half of the older adults in the community have sleep problems. Poor sleep quality was associated with symptoms of anxiety and depression. Moreover, the cortical thickness of transverse temporal gyrus may be related to anxiety symptoms in older adults with poor sleep quality. This study indicates that a decline in sleep quality may increase the risk of anxiety and depression in patients, and transverse temporal gyrus may play an important regulatory role in the above process.